The Science of Being a Study Participant: FEM-PrEP Participants' Explanations for Overreporting Adherence to the Study Pills and for the Whereabouts of Unused Pills. (15th April 2015) - Corneli, Amy L.; McKenna, Kevin; Perry, Brian; Ahmed, Khatija; Agot, Kawango; Malamatsho, Fulufhelo; Skhosana, Joseph; Odhiambo, Jacob; Van Damme, Lut
Abstract : Background: FEM-PrEP was unable to determine whether once-daily, oral emtricitabine/tenofovir disoproxil fumarate reduces the risk of HIV acquisition among women because of low adherence. Self-reported adherence was high, and pill-count data suggested good adherence. Yet, drug concentrations revealed limited pill use. We conducted a follow-up study with former participants in Bondo, Kenya, and Pretoria, South Africa, to understand factors that had influenced overreporting of adherence and to learn the whereabouts of unused pills. Methods: Qualitative, semistructured interviews were conducted with 88 participants, and quantitative, audio computer-assisted self-interviews were conducted with 224 participants. We used thematic analysis and descriptive statistics to analyze the qualitative and quantitative data, respectively. Results: In audio computer-assisted self-interviews, 31% (n = 70) said they had overreported adherence; the main reason was the belief that nonadherence would result in trial termination (69%, n = 48). A considerable percentage (35%, n = 78) acknowledged discarding unused pills. Few acknowledged giving their pills to someone else (4%, n = 10), and even fewer acknowledged giving them to someone with HIV (2%, n = 5). Many participants in the semistructured interviews said other participants had counted and removed pills from their bottles to appear adherent. Conclusions: Despite repeated messages that nonadherence would not upset staff, participants acknowledged several perceived negative consequences of reporting nonadherence, which made it difficult to report accurately. Uneasiness continued in the follow-up study, as many said they had not overreported during the trial. Efforts to improve self-reported measures should include identifying alternative methods for creating supportive environments that allow participants to feel comfortable reporting actual adherence.